DELUS. The Journal of the Institute of Landscape and Urban Studies - Prado de O. Martins, Luiza; Gruber, Christina; Reisinger, Karin; Jasper, Sandra; Pérez Villoro, Federico (DELUS. The Journal of the Institute of Landscape and Urban Studies, 2024)
The pilot issue of DELUS offers a range of diverse insights into landscape and urban questions. It introduces new methods to unpack multiple worlds and narrate manifold stories. The contributions range from unraveling histories of land-body relations through recipes with Luiza Prado de O. Martins, following living fossils and their mythical counterparts with Christina Gruber, working with communities to examine extractive environments with Karin Reisinger, exploring postnatural aesthetics with the Institute for Postnatural Studies, to recording wastelands with Sandra Jasper and developing speculative curricula engaging with overlooked forms of knowledge with Federico Pérez Villoro. As a collection, these contributions address the complex relations between humans, non-humans and their environment across time and spac